2014
DOI: 10.1073/pnas.1406357111
|View full text |Cite
|
Sign up to set email alerts
|

Form of an evolutionary tradeoff affects eco-evolutionary dynamics in a predator–prey system

Abstract: Evolution on a time scale similar to ecological dynamics has been increasingly recognized for the last three decades. Selection mediated by ecological interactions can change heritable phenotypic variation (i.e., evolution), and evolution of traits, in turn, can affect ecological interactions. Hence, ecological and evolutionary dynamics can be tightly linked and important to predict future dynamics, but our understanding of eco-evolutionary dynamics is still in its infancy and there is a significant gap betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 63 publications
7
72
0
Order By: Relevance
“…The trait range where this competitive exclusion of the undefended prey occurred was strongly reduced by the post‐attack defense, while the trait range allowing coexistence increased in comparison with a noninterfering pre‐attack defense due to indirect facilitation. The relevance of our results is supported by empirical studies revealing that low to intermediate defense levels frequently occur in nature (White, Kaul, Knoll, Wilson, & Sarnelle, 2011) and that defended prey types may outcompete undefended prey types even if they have costs for their defense (Kasada et al., 2014). The presented mechanism of indirect facilitation among prey species may provide an explanation why apparent competition, that is, an increasing density of one prey species indirectly reduces the density of the other prey species via the predator (Holt, 1977), is not always observed in nature (Chaneton & Bonsall, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trait range where this competitive exclusion of the undefended prey occurred was strongly reduced by the post‐attack defense, while the trait range allowing coexistence increased in comparison with a noninterfering pre‐attack defense due to indirect facilitation. The relevance of our results is supported by empirical studies revealing that low to intermediate defense levels frequently occur in nature (White, Kaul, Knoll, Wilson, & Sarnelle, 2011) and that defended prey types may outcompete undefended prey types even if they have costs for their defense (Kasada et al., 2014). The presented mechanism of indirect facilitation among prey species may provide an explanation why apparent competition, that is, an increasing density of one prey species indirectly reduces the density of the other prey species via the predator (Holt, 1977), is not always observed in nature (Chaneton & Bonsall, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the type of defense costs regarding competitiveness (resource uptake affinity or growth rate) plays an important role for coexistence. Theory already showed that predator‐mediated coexistence crucially depends on the environmental conditions (Chase et al., 2002), for example, the enrichment level (Genkai‐Kato & Yamamura, 1999; Leibold, 1996; Proulx & Mazumder, 1998), the prey switching behavior of the predator (Abrams & Matsuda, 1993; Fryxell & Lundberg, 1994; Murdoch, 1969), the magnitude of the trade‐off between defense and competitiveness (Abrams, 1999; Kasada, Yamamichi, & Yoshida, 2014; Tirok & Gaedke, 2010), and the difference in both the defense level and the competitiveness between the prey types (Becks, Ellner, Jones, & Hairston, 2010; Ehrlich, Becks, & Gaedke, 2017; Jones & Ellner, 2007). However, the role of different defense mechanisms and competition costs in prey communities remains unclear but holds promise to be decisive for their coexistence and the occurring population dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this perspective has recently received much attention (e.g., refs. [5][6][7][8], little is known about how interactions between organismal traits and biotic as well as abiotic drivers of ecosystem change govern the occurrence and strength of these feedbacks (9).…”
mentioning
confidence: 99%
“…Plankton microcosms have been used previously to study eco-evolutionary dynamics, e.g., how prey evolution alters the population-level dynamics of predator-prey systems (Yoshida et al 2003, Becks et al 2010, Kasada et al 2014). Plankton microcosms have been used previously to study eco-evolutionary dynamics, e.g., how prey evolution alters the population-level dynamics of predator-prey systems (Yoshida et al 2003, Becks et al 2010, Kasada et al 2014).…”
Section: Co-occurrence Of Increased Extinction Thresholds and Hydra Ementioning
confidence: 99%